2018
DOI: 10.1109/tip.2018.2859628
|View full text |Cite
|
Sign up to set email alerts
|

BiggerSelfie: Selfie Video Expansion With Hand-Held Camera

Abstract: Selfie photography from the hand-held camera is becoming a popular media type. Although being convenient and flexible, it suffers from low camera motion stability, small field of view, and limited background content. These limitations can annoy users, especially, when touring a place of interest and taking selfie videos. In this paper, we present a novel method to create what we call a BiggerSelfie that deals with these shortcomings. Using a video of the environment that has partial content overlap with the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…e wavelet transform [14][15][16][17] is an effective denoising method related to regularized inversion. In this study, wavelet transform is utilized to decompose and extract the low-and high-frequency information of the blurred image, which is taken as the critical step of the presented deblurring methods.…”
Section: Blurred Li-style Boat-shaped House Restorationmentioning
confidence: 99%
“…e wavelet transform [14][15][16][17] is an effective denoising method related to regularized inversion. In this study, wavelet transform is utilized to decompose and extract the low-and high-frequency information of the blurred image, which is taken as the critical step of the presented deblurring methods.…”
Section: Blurred Li-style Boat-shaped House Restorationmentioning
confidence: 99%
“…It has been observed that introducing semantic cues to exemplar-based image completion helps to obtain plausible results. Such cues can be specified by user interaction [25,26] or extracted from some large-scale dataset like Internet images [27][28][29][30]. Then exemplar patches are selected and aligned to satisfy the cues such that the completed holes are a good match to the context of the entire image.…”
Section: Image and Video Completionmentioning
confidence: 99%
“…Recently, unstructured video stitching methods have been explored [22,46,47]. Lai et al [22] proposed a neural network for video captured by a linear camera array (see Fig.…”
Section: Panoramic Image and Video Creationmentioning
confidence: 99%